Social (in)Justice, or the Condition of Global Capitalism in the Lost Child (2015) by Caryl Phillips - Frątczak-Dąbrowska, Marta (Studia Anglica Posnaniensia, 2019)
The present article is a critical rereading of Caryl Phillips’s latest novel The Lost Child (2015). It looks at the text as both a literary comment on the crisis of today’s global capitalism and as an acute socio-economic analysis of the crisis’ roots and effects. It is being argued that, by placing Wuthering Heights (1847) as an intertext for his contemporary novel and by linking the figure of Heathcliff with African slavery and contemporary poverty, Caryl Phillips aims to emphasise the affinity between the socio-economic conditioning of the nineteenth- and twentieth-century England, as well as between the contemporary and historical experience of economic marginalisation. Thus, he shows global capitalism as a universal experience of long modernity and asks some vital questions about its shape and its future. The following analysis, in line with recent scholarship in the field of postcolonial studies, combines postcolonial criticism with socioeconomic theories and argues that the novel deserves a place in the ongoing debates on the condition of the global economy, social (in)justice and (in)equality, which nowadays become part of the postcolonial literary scholarship.